EFFECT OF E-PROCUREMENT ON EFFECTIVE SUPPLY CHAIN MANAGEMENT PROCESS IN ENERGY SECTOR IN KENYA - Ngeno, Kipngetich; Kinoti, Dr. Justus (International Journal of Supply Chain Management, 2017)
Purpose: The purpose of the study is to assess the effect e-procurement on effective supply chain management process in energy sector in Kenya. Methodology: The study apply the research design where both qualitative and quantitative techniques was used. The study aims at collating and collecting information from the respondents. The study employ stratified random sampling technique in coming up with sample size of 152 respondents from a total of 246 target population in the energy sector. The questionnaires were circulated to all the respondents with the help of researcher. The study used Slovin's fomula: n=N/ (1+e2) in sampling while Semi-structured questionnaire was used to collect data. Pilot study was carried out to establish the reliability and validity of the research instruments. The data were organized, edited, analyzed and interpreted using descriptive and inferential statistics with the help of statistical package for social sciences version 21. The data was analyzed and presented through a form of tables, figures, pie charts and bar charts followed by the presentation, interpretation and discussion of the findings. Results: All the variables, that is, electronic data interchange, e-tendering, supply chain integration were found to have influence on effective supply chain management process on energy sector. Unique Contribution to Theory Practice and policy: The study recommended that a similar research should be conducted with an aim at investigating the effects of e-procurement on supply chain management process with other variables or of other firms in other sectors, including the products industry in the Kenyan market.